Business Process Management 11th International Conference, BPM 2013, Beijing, China, August 26-30, 2013. Proceedings - Daniel, Florian; Wang, Jianmin; Weber, Barbara; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the proceedings of the 11th International Conference on Business Process Management, BPM 2013, held in Beijing, China, in August 2013. The 17 regular papers and 8 short papers included in this volume were carefully reviewed and selected from 118 submissions. The papers are organized in 7 topical sections named: process mining; conformance checking; process data; process model matching; process architectures and collaboration; as well as alternative perspectives, and industry paper.
Keynotes -- Moneyball for nanoHUB: Theory-driven and Data-driven Approaches to understand the Formation and Success of Software Development Teams -- Towards the Next Generation Intelligent BPM - In the Era of Big Data -- BPM In The Cloud -- Process mining -- Bridging Abstraction Layers in Process Mining by automated Matching of Events and Activities -- Mining Configurable Process Models from Collections of Event Logs -- Slice, Mine and Dice: Complexity-Aware Automated Discovery of Business Process Models -- Business Process Mining from Ecommerce Web logs -- Discovering Data-Aware Declarative Process Models from Event Logs -- Enhancing Declare Maps Based on Event Correlations -- Conformance checking -- Aligning Event Logs and Process Models for Multi-Perspective Conformance Checking: An Approach Based on Integer Linear Programming -- Conformance Checking in the Large: Partitioning and Topology -- On Enabling Compliance of Cross-organizational Business Processes -- Process data -- Verification of Query Completeness over Processes -- Modeling and Enacting Complex Data Dependencies in Business Processes -- Event Stream Processing Units in Business Processes -- Process model matching -- Predicting the Quality of Process Model Matching -- Increasing Recall of Process Model Matching by Improved Activity Label Matching -- A Visualization Approach for Difference Analysis of Process Models and Instance Traffic -- Process architectures and collaboration -- Business Process Architectures with Multiplicities: Transformation and Correctness -- Optimal resource assignment in workflows for maximizing cooperation -- Accelerating Collaboration in Task Assignment Using a Socially Enhanced Resource Model -- Alternative perspectives -- Splitting GSM Schemas: A Framework for Outsourcing of Declarative Artifact Systems -- Composing Workflow Activities on the Basis of Dataflow Structures -- Mixing Paradigms for More Comprehensible Models -- Industry papers -- An Agile BPM Project Methodology -- Declarative Modeling - An Academic Dream or the Future for BPM? -- Investigating Clinical Care Pathways Correlated With Outcomes -- Exformatics Declarative Case Management Workflows as DCR Graphs.
Keywords: Economics; Software engineering; Logic design; Information systems; Information Systems; Management information systems; Economics/Management Science; Business Information Systems; Logics and Meanings of Programs; Software Engineering; Computer Appl. in Administrative Data Processing; Management of Computing and Information Systems